Indian diabetes risk profile of employees in a tertiary care facility in north Maharashtra: a cross sectional study - Ashtekar, Shyam V.; Singh, Aryaman; Padhyegurjar, Manasi S.; Shaikh, Sidrah M.; Kapse, Abhimanyu R.; Thorat, Devendra R.; Bele, Rahul R.; Dhatare, Pushpak D.; Sharif, Ashhar Ahmed; Rajput, Abhimanyu (International Journal Of Community Medicine And Public Health, 2021)
Background: The rising prevalence of type 2 diabetes (T2D) in India calls for screening of at-risk adults. Objectives were to assess IDRS (Indian diabetes risk score) of T2D in staff in tertiary care hospital, and to assess covariates random blood sugar (RBS), BMI, skinfold thickness (SFT), pre-existing T2D in the employees. Methods: In this cross sectional study, IDRS was used to assess all staff in a tertiary care institute. Anthropometric measurements, BP and RBS were done. Information on parental T2D, cereal intake and weekly physical activity (PA) was obtained in interview. Results: 370 subjects (F-117, M-273) with mean age 30.81 (7.99), BMI 22.89 (14.13) years were screened. Subjects in moderate and sedentary work were 185 each, 15% women and 39% men had higher waist size. Total 5.4% subjects had T2D including known diabetics. RBS in women and men was 113.1 (27.87), 114.7 (27.66), with IDRS score high in 29 (7.84%) and moderate in 144 (38.92%). Parental T2D was present in 19.5% subjects. IDRS risk was strongly associated with type of work (Chi-square 79.0283, df=4, p=0.00). Multiple logistic regression for IDRS risk outcome showed association of age (OR 1.4), BMI (OR1.3), parental T2D (OR 9.6) with highly significant p values. Multiple linear regression for RBS outcome was associated with age (OR 1.3) and BMI (OR 1.4) but the results were statistically not significant. Conclusions: Pooled IDRS risk was present in 47% subjects despite younger age of study population. Improvements in physical activity and reduction in waist size is the need of the hour.